Investigating the Relationship between Organizational Culture and Employees Job Satisfaction - Keshavarz, Yousef; Jamshidi, Dariyoush (IJRDO - Journal of Business Management, 2017)
The main purpose of this study is to examine the relationship between the dimensions of organizational culture and employee job satisfaction at Islamic Azad University (IAU) which is located at Iran, region one. The population comprised of all employees of 31 branches of IAU located at region one. Data was collected by structured questionnaire, designed based on the Robbins’ 10 criteria indexes, through 550 respondents who selected randomly through clustering sampling. Two types of statistical testing were employed, descriptive and inferential statistics. Correlation analysis was used to test the relationships between dimensions of organizational cultures with job satisfaction. The results showed that there is a significant and positive relationship between organization identity, managerial support, risk taking ability, participation, organizational communication, control and organizational integration with job satisfaction. However, the relationship between individual creativity, conflict, and reward system with job satisfaction was not supported in this study. The result of this study is useful for managers to increase productivity in the company by the factors of organizational culture.